Propagation of three Blue Honeysuckle (Lonicera caerulea L.) cultivars in in vitro culture Razmnožavanje tri kultivara sibirske borovnice u in vitro kulturi - Mihaljević, Ines; Tomaš, Vesna; Vuković, Dominik, agronom; Dugalić, Krunoslav (2019)
The aim of this study was to micropropagate three blue honeysuckle cultivars "Kalinka", "Polar Jewell" and "Balalaika". Driver and Kuniyuki medium (DKW) with different type and concentrations of plant hormones for in vitro shoot multiplication. For in vitro rooting was used Driver and Kuniyuki medium (DKW) and Murashige and Skoog medium (MS) with different concentrations of indol-3-butyric acid (IBA). The highest multiplication rate was obtained on DKW medium supplemented with 4 mg L-1 6-benzylaminopurine (BA) and 1 mg L-1 indole-3-butyric acid (IBA) for cultivars "Balalaika" and "Polar Jewell", while of cultivar "Kalinka" with DKW medium and 2 mg L-1 6-benzylaminopurine (BA) and 0.5 mg L-1 indole-3-butyric acid (IBA). The best microshoot rooting rates were obtained on DKW basal nutrient medium with 1 mg L-1 indol-3-butyric acid (IBA).
Cilj ovog istraživanja bio je razviti protokol za mikrorazmnožavanje triju kultivara sibirske borovnice "Kalinka", "Polar Jewell" i "Balalaika". Medij Driver i Kuniyuki (DKW) s različitim vrstama i koncentracijama biljnih hormona korišten je za multiplikaciju izdanaka. Za in vitro ukorjenjivanje korišteni su medij Driver i Kuniyuki (DKW) te medij Murashige i Skoog (MS) s različitim koncentracijama indol 3-maslačne kiseline (IBA). Najviša stopa multiplikacije je postignuta na DKW mediju sa 4 mg L-1 6-benzilaminopurina (BAP) i 1 mg L-1 indol 3-maslačne kiseline (IBA) kod kultivara "Balalaika" i "Polar Jewel", dok je kod kultivara "Kalinka" najviša multiplikacija postignuta na DKW mediju s 2 mg L-1 6-benzilaminopurina (BAP) i 0.5 mg L-1 indol 3-maslačne kiseline (IBA). Najbolje ukorjenjivanje mikro izdanaka postignuto je na DKW mediju s 1 mg L-1 indol 3-maslačne kiseline (IBA).
Bibliografija: str. 47-48.
Abstract ; Sažetak.
Keywords: Sibirska borovnica -- Mikropropagacija -- In vitro -- Ukorjenjivanje